ANALISIS KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN MENGGUNAKAN METODE CUSTOMER SATISFACTION INDEX (CSI) DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) PADA OPTIK “JAKARTA” PEKANBARU - Teddy Chandra; Devy Novia (Institut Bisnis dan Teknologi Pelita Indonesia, 2019)
The purpose of this study was to determine and analyze the level of satisfaction of each attribute based on the Customer Satisfaction Index (CSI) method and determine the level of consumer interest based on the Importance Performance Analysis (IPA) method. This study uses 5 (five) SERVQUAL dimensions, namely tangible, reliability, responsiveness, empathy and assurance. This study uses a sample of 108 respondents who are consumers of Optical